The social activity of the ladies of the royal family (Journal of the College of Basic Education, 2022)
The women of the royal family in Iraq played a major fundamental role that greatly influenced the current events in Iraq despite the difficult circumstances in which women were the main reason for the development of Iraqi women due to their support for the women's movement in Iraq and their encouragement of education in particular.